Spondin 2 promotes the proliferation, migration and invasion of gastric cancer cells - Lu, Haoming (J Cell Mol Med, 2019)
Spondin 2 (SPON2), a member of the Mindin F‐Spondin family, identifies pathogens, activates congenital immunity and promotes the growth and adhesion of neurons as well as binding to their receptors, but its role in promoting or inhibiting tumour metastasis is controversial. Here, we investigated its expression levels and mechanism of action in gastric cancer (GC). Western blotting and GC tissue arrays were used to determine the expression levels of SPON2. ELISAs were performed to measure the serum levels of SPON2 in patients with GC. Two GC cell lines expressing low levels of SPON2 were used to analyse the effects of regulating SPON2 expression on proliferation, migration, invasion, the cell cycle and apoptosis. The results revealed that SPON2 was highly expressed in GC tissues from patients with relapse or metastasis. The levels of SPON2 in sera of patients with GC were significantly higher compared with those of healthy individuals and patients with atrophic gastritis. Knockdown of SPON2 expression significantly inhibited the proliferation, migration and invasion of GC cells in vitro and in vivo. Down‐regulation of SPON2 arrested the cell cycle in G1/S, accelerated apoptosis through the mitochondrial pathway and inhibited the epithelial‐mesenchymal transition by blocking activation of the ERK1/2 pathway. In summary, this study suggests that SPON2 acts as an oncogene in the development of GC and may serve as a marker for the diagnosing GC as well as a new therapeutic target for GC.